The clinical utility of multimodal MR image-guided needle biopsy in cerebral gliomas. (2nd January 2016) - Yao, Chengjun; Lv, Shunzeng; Chen, Hong; Tang, Weijun; Guo, Jun; Zhuang, Dongxiao; Chrisochoides, Nikos; Wu, Jinsong; Mao, Ying; Zhou, Liangfu
Abstract : Purpose : Our aim was to evaluate the diagnostic value of multimodal Magnetic Resonance (MR) Image in the stereotactic biopsy of cerebral gliomas, and investigate its implications. Materials and Methods : Twenty-four patients with cerebral gliomas underwent 1 H Magnetic Resonance Spectroscopy ( 1 H-MRS)- and intraoperative Magnetic Resonance Imaging (iMRI)-supported stereotactic biopsy, and 23 patients underwent only the preoperative MRI-guided biopsy. The diagnostic yield, morbidity and mortality rates were analyzed. In addition, 20 patients underwent subsequent tumor resection, thus the diagnostic accuracy of the biopsy was further evaluated. Results : The diagnostic accuracies of biopsies evaluated by tumor resection in the trial groups were better than control groups (92.3% and 42.9%, respectively, p = 0.031). The diagnostic yield in the trial groups was better than the control groups, but the difference was not statistically significant (100% and 82.6%, respectively, p = 0.05). The morbidity and mortality rates were similar in both groups. Conclusions : Multimodal MR image-guided glioma biopsy is practical and valuable. This technique can increase the diagnostic accuracy in the stereotactic biopsy of cerebral gliomas. Besides, it is likely to increase the diagnostic yield but requires further validation.